Method for producing magnetic particles, magnetic particles, and permanent magnet using same

Manganese particles are treated by high-temperature aluminization, and the gap of anti-sintering agent is used to reduce adhesion, simplifying the manufacturing process of manganese-aluminum alloy magnetic particles, solving the existing complicated processes, and achieving simple separation and recycling of magnetic particles.

CN119300932APending Publication Date: 2025-01-10AGC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380043568.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-05-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing process for manufacturing manganese-aluminum alloy magnetic particles containing the T-phase is complicated and there is a lack of simple methods.

Method used

By mixing manganese particles, aluminum source and halide activator with anti-sintering agent, aluminized treatment is carried out at high temperature, and the gap formed by the anti-sintering agent is used to reduce adhesions, so as to achieve the formation and separation of manganese-aluminum alloys.

Benefits of technology

It is possible to easily manufacture manganese-aluminum alloy magnetic particles containing the t-phase, and the magnetic particles can be easily separated and recovered, avoiding the formation of bulk aggregation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300932A_ABST
    Figure CN119300932A_ABST
Patent Text Reader

Abstract

A method for producing magnetic particles comprising a manganese-aluminum alloy, in which a mixed powder is obtained by mixing manganese particles, an aluminum source, and an activator comprising a halide with an anti-sintering agent, then the mixed powder is heated, the manganese particles are aluminized using gaps between the anti-sintering agents formed by the anti-sintering agent, and the aluminized manganese particles are sintered to form the magnetic particles. The method is characterized in that a treated mixture containing magnetic particles containing a manganese-aluminum alloy is obtained, the ratio of aluminum to manganese (Al / Mn) in the manganese-aluminum alloy is in the range of 25 / 75-35 / 65 by mass ratio, the anti-sintering agent is removed from the treated mixture, and the magnetic particles containing the manganese-aluminum alloy are recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing magnetic particles and magnetic particles. Background Art

[0002] Conventionally, it is known that magnetic particles of a manganese-aluminum alloy including a ferromagnetic phase τ phase can be used as a magnetic material.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2019-44265 Summary of the invention

[0006] Generally speaking, magnetic particles of a manganese-aluminum alloy containing a τ phase are produced by the following steps:

[0007] (1) Forming powder by melt-blowing method, etc.

[0008] (2) fine powdering by crushing the powder, and

[0009] (3) Aging treatment of fine powder.

[0010] In the treatment (1), a large-diameter powder mainly composed of the ε phase is formed. Therefore, the powder is refined by the treatment (2), and the heat treatment (aging treatment) is performed to transform the ε phase into the τ phase by the treatment (3).

[0011] However, such a production process is complicated, and there is a need for a method of producing magnetic particles of a manganese-aluminum alloy containing a τ phase in a simpler way.

[0012] The present invention has been made in view of such background, and an object of the present invention is to provide a method for more simply producing magnetic particles made of a manganese-aluminum alloy. Another object of the present invention is to provide magnetic particles made of a manganese-aluminum alloy obtained by such a characteristic process.

[0013] The present invention provides a method for producing magnetic particles comprising a manganese-aluminum alloy.

[0014] The manganese particles, the aluminum source, and the activator containing the halide and the anti-sintering agent are mixed to obtain a mixed powder.

[0015] The mixed powder is heated to a temperature in the range of 1000° C. to 1235° C., and the manganese particles are subjected to aluminizing treatment using gaps between the sintering inhibitors formed by the sintering inhibitors to obtain a treated mixture having magnetic particles containing a manganese-aluminum alloy.

[0016] In the above manganese-aluminum alloy, the ratio of aluminum to manganese (Al / Mn) is in the range of 25 / 75 to 35 / 65 by mass ratio.

[0017] The anti-sintering agent is removed from the treated mixture to recover the magnetic particles comprising the manganese-aluminum alloy.

[0018] In addition, the present invention provides a magnetic particle comprising a manganese-aluminum alloy and aluminum oxide.

[0019] The aluminum oxide contained in the magnetic particles has a content in the range of 0.1 mass % to 15 mass %.

[0020] The manganese-aluminum alloy contained in the magnetic particles has a content in the range of 85 mass % to 99 mass %.

[0021] The above-mentioned manganese-aluminum alloy has a τ phase,

[0022] The abundance ratio of the τ phase contained in the magnetic particles is in the range of 25 mass % to 99 mass %.

[0023] The present invention can provide a method for more easily producing magnetic particles made of a manganese-aluminum alloy. In addition, the present invention can provide magnetic particles made of a manganese-aluminum alloy obtained by such a characteristic process. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a diagram schematically showing an example of the flow of a method for producing magnetic particles according to one embodiment of the present invention.

[0025] Figure 2 This is a diagram schematically showing how the mixed powder is filled in a reaction container.

[0026] Figure 3 This is a graph showing an example of X-ray diffraction results of a powder (powder A-1) containing magnetic particles according to one embodiment of the present invention.

[0027] Figure 4 This is a diagram showing the results of mapping oxygen and aluminum in the cross section of magnetic particles (particles contained in powder A-1) according to one embodiment of the present invention. DETAILED DESCRIPTION

[0028] An embodiment of the present invention is described below.

[0029] In one embodiment of the present invention, a method for producing magnetic particles comprising a manganese-aluminum alloy is provided.

[0030] The manganese particles, the aluminum source, and the activator containing the halide and the anti-sintering agent are mixed to obtain a mixed powder.

[0031] The mixed powder is heated to a temperature in the range of 1000° C. to 1235° C., and the manganese particles are subjected to aluminizing treatment using gaps between the sintering inhibitors formed by the sintering inhibitors to obtain a treated mixture having magnetic particles containing a manganese-aluminum alloy.

[0032] In the above manganese-aluminum alloy, the ratio of aluminum to manganese (Al / Mn) is in the range of 25 / 75 to 35 / 65 by mass ratio.

[0033] The anti-sintering agent is removed from the treated mixture to recover the magnetic particles comprising the manganese-aluminum alloy.

[0034] In one embodiment of the present invention, magnetic particles made of a manganese-aluminum alloy including a ferromagnetic τ phase are produced by aluminizing.

[0035] Aluminizing is a technique for diffusing aluminum from the surface of a treated object to the inside at high temperature. When manganese particles are used as the treated object, aluminum can penetrate into the manganese particles during aluminizing to form a manganese-aluminum alloy. Therefore, by setting the ratio of manganese to aluminum and the temperature in the reaction system to a predetermined range in advance, a manganese-aluminum alloy can be formed after the treatment.

[0036] In one embodiment of the present invention, magnetic particles containing a manganese-aluminum alloy containing a τ phase can be produced by a single process without going through the multiple steps (1) to (3) described above. Therefore, in one embodiment of the present invention, magnetic particles containing a manganese-aluminum alloy can be produced by a simpler process than before.

[0037] It should be noted that if aluminizing is applied to a workpiece containing a trace amount of oxygen, reduction of oxides in the workpiece and oxidation of aluminum may occur, resulting in a solid-phase contact reaction (aluminothermic reaction) accompanied by intense heat release. If such aluminothermic reaction occurs, the heat causes the reaction to proceed rapidly, and there is no time for the heat to diffuse to the outside. As a result of heat storage, the reaction system may reach a temperature of several thousand degrees Celsius.

[0038] Therefore, when the object to be processed is in the form of particles, if thermite reaction occurs, the processing environment becomes extremely hot, and the mixture after processing (hereinafter referred to as "processed mixture") becomes a block-like form in which all particles are firmly bonded to each other.

[0039] Furthermore, once such a bulky treated mixture is generated, the anti-sintering agent cannot be separated from the treated mixture thereafter. Therefore, there is a problem that the aluminized particles cannot be recovered from the treated mixture.

[0040] However, in the method according to one embodiment of the present invention, the aluminizing treatment is performed using the gaps formed between the sintering inhibitors.

[0041] According to such a feature, in the method according to one embodiment of the present invention, even if thermite reaction occurs in the reaction system, the possibility of adhesion between manganese particles and anti-sintering agents etc. is greatly reduced. This is because the above-mentioned gap plays the role of providing a plurality of "small partitions" for reactions separated from each other.

[0042] As a result, the treated mixture generated after the aluminizing treatment does not become a whole agglomerated mass, but becomes a state in which the magnetic particles containing the manganese-aluminum alloy and the anti-sintering agent are separated from each other. Therefore, in the method according to one embodiment of the present invention, after the aluminizing treatment, the anti-sintering agent can be relatively easily removed from the treated mixture. In addition, thereby, the magnetic particles containing the manganese-aluminum alloy can be relatively easily separated and recovered.

[0043] As described above, in the method according to one embodiment of the present invention, magnetic particles including a manganese-aluminum alloy can be easily produced and easily separated and recovered.

[0044] (Method for producing magnetic particles according to one embodiment of the present invention)

[0045] Next, refer to Figure 1 A method for producing magnetic particles according to one embodiment of the present invention will be described in detail.

[0046] Figure 1 An example of a flow of a method for producing magnetic particles according to an embodiment of the present invention is schematically shown in FIG.

[0047] like Figure 1 As shown, a method for producing magnetic particles according to one embodiment of the present invention (hereinafter referred to as "first production method") comprises the following steps:

[0048] a step of mixing manganese particles, an aluminum source, an activator containing a halide, and a sintering inhibitor to obtain a mixed powder (step S110);

[0049] A step of heating the mixed powder to aluminize the manganese particles to obtain a treated mixture having magnetic particles containing a manganese-aluminum alloy (step S120); and

[0050] A step of removing the anti-sintering agent from the treated mixture (step S130).

[0051] Each process is described in more detail below.

[0052] (Process S110)

[0053] First, a mixed powder is prepared.

[0054] The mixed powder contains manganese particles, an aluminum source, an activator, and an anti-sintering agent. Each component is described below.

[0055] (Manganese particles)

[0056] The average particle size of the manganese particles is selected so as to be smaller than the average particle size of the sintering inhibitor described below. For example, the maximum particle size of the manganese particles may be 0.29 times or less of the average particle size of the sintering inhibitor.

[0057] The average particle size of the manganese particles can be, for example, in the range of 5 μm to 300 μm, in the range of 10 μm to 200 μm, or in the range of 10 μm to 50 μm. When the average particle size of the manganese particles is small, the diffusion distance of Al becomes shorter, and the heat treatment time can be shortened. In addition, if the average particle size of the magnetic particles containing the manganese-aluminum alloy after the aluminizing treatment becomes smaller, it is easy to increase the packing density during molding and easy to mold into a desired shape.

[0058] In addition, in this application, "average particle size" means the thing measured by the method prescribed|regulated in JIS Z 8801.

[0059] That is, multiple sieves with different apertures are stacked in order from the smallest aperture, and the particles to be measured are vibrated for a certain time and a certain amplitude to screen the particles. Next, the mass of the particles remaining on each sieve is measured, and the particle size distribution of the particle mass is plotted. The particle size at which the cumulative value of the obtained particle size distribution is equivalent to 50% is defined as the "average particle size".

[0060] (Aluminum source)

[0061] The aluminum source may be aluminum metal particles or aluminum alloy particles.

[0062] The average particle size of the aluminum source is selected so as to be smaller than the average particle size of the sintering inhibitor. For example, the average particle size of the aluminum source may be 0.29 times or less of the average particle size of the sintering inhibitor.

[0063] The average particle size of the aluminum source may be, for example, in the range of 0.1 μm to 300 μm, 1 μm to 200 μm, or 1 μm to 100 μm. If the average particle size of the aluminum source is small, it is easy to enter the gaps between the sintering inhibitors, and the heat treatment time can be shortened.

[0064] (Activator)

[0065] The activator has a function of forming a vapor of a metal halide during aluminizing of the manganese particles to promote the aluminizing.

[0066] The activator includes, for example, at least one of ammonium chloride, aluminum chloride, and aluminum fluoride. For example, the activator is added in a range of 0.1 mass % to 10 mass % relative to the entire mixed powder.

[0067] (Anti-sintering agent)

[0068] The sintering inhibitor may include at least one of alumina, kaolin, and silica.

[0069] The sintering inhibitor may have at least one shape selected from the group consisting of, for example, a spherical shape, a triangular pyramid shape, a triangular prism shape, a tetrahedron shape, a cone shape, and a cylindrical shape.

[0070] The sintering inhibitor has an average particle size sufficiently larger than that of the manganese particles and the aluminum source. For example, the sintering inhibitor is selected so that the average particle size is 3.4 times or more the maximum particle size of the manganese particles and the average particle size of the aluminum source.

[0071] The average particle size of the sintering inhibitor may be in the range of, for example, 50 μm to 5000 μm.

[0072] (Mixed powder)

[0073] A mixed powder is prepared by mixing the above-mentioned components.

[0074] The amount of manganese particles contained in the mixed powder as a whole is, for example, in the range of 3 mass % to 45 mass %. In addition, the amount of aluminum source contained in the mixed powder as a whole is, for example, in the range of 1 mass % to 15 mass %. In addition, the amount of the anti-sintering agent contained in the mixed powder as a whole can be appropriately adjusted according to the amount of manganese particles and the amount of aluminum source, for example, in the range of 40 mass % to 96 mass %.

[0075] The aluminum source is added to the mixed powder so that the mass ratio (Al / Mn) of aluminum to manganese contained in the produced manganese-aluminum alloy particles is within a range of 25 / 75 to 35 / 65.

[0076] (Process S120)

[0077] Next, the mixed powder prepared in step S110 is subjected to a heat treatment, so that the mixed powder can be filled into a reaction container.

[0078] By heating the reaction container, the manganese particles are subjected to aluminizing treatment, that is, aluminum generated from the aluminum source diffuses and penetrates into the manganese particles to form magnetic particles containing a manganese-aluminum alloy.

[0079] Here, when the reaction container is heated, a large amount of heat is generated by thermite reaction between the mixed powders. This is because aluminum reacts with a small amount of oxygen contained in the manganese particles.

[0080] If such a thermite reaction occurs, the temperature in the reaction vessel becomes extremely high, and the treated mixture, i.e., the "treated mixture", may become a block-like form in which all particles are firmly adhered to each other. In addition, once such a block-like treated mixture is generated, there will be a problem that the anti-sintering agent cannot be separated from the treated mixture.

[0081] In contrast, in the first production method, the formation of a lump-shaped mixture can be significantly suppressed.

[0082] The following reference Figure 2 This feature will be described.

[0083] Figure 2 An example of the state of the mixed powder when filled into the reaction container is schematically shown in FIG. Figure 2 As shown, manganese particles 352, an aluminum source 354, an activator, and a sintering inhibitor 358, which are components of a mixed powder, are respectively filled in a reaction container.

[0084] It should be explained that Figure 2 The activator is omitted. In addition, it is assumed that each component of the mixed powder is spherical.

[0085] Here, when the diameter of the sintering inhibitor 358 (denoted by φ S ) and the diameter of the manganese particle 352 (denoted by φ Mn ) and the diameter of the aluminum source 354 (denoted by φ Al When the ratio is sufficiently large (indicated by ), a gap 365 is generated between adjacent anti-sintering agents 358. In addition, the manganese particles 352 and the aluminum source 354 are arranged in the gap 365 generated by the anti-sintering agent 358.

[0086] When the reaction container is heated in a state where the components of the mixed powder are arranged in this way, even if thermite reaction occurs in the reaction container, the possibility of the manganese particles 352 adhering to the anti-sintering agent 358 and / or other manganese particles 352 can be greatly reduced. This is because the gaps 365 play the role of providing a plurality of "small partitions" for the reaction for the aluminizing treatment.

[0087] As a result, the processed mixture generated after the heat treatment does not become agglomerated as a whole, but becomes a state in which the magnetic particles containing the manganese-aluminum alloy and the anti-sintering agent 358 are separated from each other. Therefore, the magnetic particles containing the manganese-aluminum alloy can be recovered from the processed mixture in a subsequent step.

[0088] It should be noted that the filling rate of the anti-seizing agent 358 is preferably in the range of 50% to 80%.

[0089] In this manner, in the first manufacturing method, the aluminizing treatment of the manganese particles 352 can be performed by utilizing the gaps 365 generated between the sintering inhibitors 358 .

[0090] The treatment atmosphere of the aluminizing treatment may be any atmosphere not containing oxygen, such as an argon gas atmosphere.

[0091] The treatment temperature is in the range of 1000° C. to 1235° C., preferably in the range of 1150° C. to 1230° C., and more preferably in the range of 1190° C. to 1225° C. If the treatment temperature is low, the amount of τ phase generated is small, and if the treatment temperature is too high, the phase aggregates.

[0092] The retention time at the maximum temperature is, for example, 0.5 hours or more, preferably 10 hours or more, and more preferably 20 hours or more.

[0093] The cooling after the treatment may be controlled by controlling the cooling rate in addition to furnace cooling. The cooling rate may be, for example, between 0.01°C / min and 100°C / min. However, the temperature may be temporarily maintained at a predetermined temperature during cooling.

[0094] The cooling temperature can be controlled in stages.

[0095] The pressure in the reaction container is, for example, in the range of 1 to 30 atmospheres, preferably 1.5 atmospheres or more, more preferably 2 atmospheres or more, and even more preferably 3 atmospheres or more.

[0096] The pressure is preferably 30 atmospheres or less, more preferably 20 atmospheres or less, and even more preferably 10 atmospheres or less.

[0097] The treatment pressure can be increased by closing the reaction vessel used in the reaction. In this case, for example, the pressure in the reaction vessel can be increased by gasifying the activator. Such an activator can include at least one of ammonium chloride, aluminum chloride and aluminum fluoride.

[0098] Alternatively, the pressure in the reaction vessel can be increased by filling the reaction vessel with additional gas. In this case, the additional gas can be selected from inert gas, hydrogen or chlorine.

[0099] The activator may be added in an amount within a range of 0.5% by mass to 15% by mass based on the entire mixed particles.

[0100] It should be noted that the temperature and pressure can be controlled independently.

[0101] (Process S130)

[0102] Next, the anti-sintering agent is removed from the powdered processed mixture formed in step S120. The anti-sintering agent can be removed by sieving the processed mixture using a sieve through which only particles with a small average particle size can pass, for example.

[0103] As described above, in the first production method, it is possible to significantly suppress the temperature increase of the reaction system due to the thermal storage of excess heat generated in the thermite reaction.

[0104] Therefore, in the first production method, the sintering inhibitor and the magnetic particles including the manganese-aluminum alloy can be separated relatively easily.

[0105] Through the above steps, in the first production method, magnetic particles made of a manganese-aluminum alloy can be suitably produced through a single processing step.

[0106] It should be noted that the first production method has a feature that a small amount of aluminum oxide is contained in the obtained magnetic particles.

[0107] This is considered to be because part of the aluminum constituting the manganese-aluminum alloy was oxidized during the aluminizing treatment.

[0108] The amount of aluminum oxide contained in the produced magnetic particles is in the range of 0.1% by mass to 15% by mass, and can be in the range of 1% by mass to 10% by mass, based on the weight of the magnetic particles.

[0109] In addition, the amount of manganese-aluminum alloy contained in the magnetic particles is in the range of 85 mass % to 99 mass %, and can be in the range of 86 mass % to 98 mass %. In addition, as compounds other than the above, compounds formed by combining part or all of Mn, Al, and O may also be included. In addition, as inevitable impurities, for example, nitrogen, chlorine, phosphorus, sulfur, silicon, zinc, iron, boron, and carbon, as well as their oxides, nitrides, carbides, and their composites can be cited.

[0110] In the manganese-aluminum alloy contained in the magnetic particles, the τ phase may be in the range of 25 to 99 mass % relative to the manganese-aluminum alloy, preferably 30 mass % or more, more preferably 50 mass % or more relative to the manganese-aluminum alloy.

[0111] The manganese-aluminum alloy included in the magnetic grains may include at least one of the ε phase, the β phase, and the γ phase in addition to the τ phase.

[0112] It should be noted that in the present application, the τ phase refers to the tetragonal structure of MnAl. In addition, the ε phase refers to the hexagonal structure of MnAl, and the β phase refers to the 3 Al 2 The cubic structure of the γ phase refers to Mn 5 Al 8Rhombohedral crystal structure.

[0113] Among them, the ε phase is preferably present in an amount of 10 mass % or less based on the entire manganese-aluminum alloy.

[0114] (Magnetic Particles According to One Embodiment of the Present Invention)

[0115] Next, magnetic particles according to one embodiment of the present invention will be described.

[0116] In one embodiment of the present invention, there is provided a magnetic particle comprising a manganese-aluminum alloy and aluminum oxide.

[0117] The aluminum oxide contained in the magnetic particles has a content in the range of 0.1 mass % to 15 mass %.

[0118] The manganese-aluminum alloy contained in the magnetic particles has a content in the range of 85 mass % to 99 mass %.

[0119] The above-mentioned manganese-aluminum alloy has a τ phase,

[0120] The abundance ratio of the τ phase contained in the magnetic particles is in the range of 25 mass % to 99 mass %.

[0121] The abundance ratio of the τ phase is, for example, 50 mass % or more, preferably 60 mass % or more, and more preferably 70 mass % or more.

[0122] In one embodiment of the present invention, in the τ phase contained in the magnetic particles, the a-axis of the lattice may be greater than the a-axis value of Al0.89Mn1.11 (PDF01-071-5837) registered in the ICDD database. (hereinafter referred to as "the a-axis value of the database") short.

[0123] For example, the a-axis may be more than 0.2% shorter than the a-axis value of the database.

[0124] In addition, in the τ phase contained in the magnetic particles, the C axis of the lattice can be compared with the C axis value of Al0.89Mn1.11 (PDF01-071-5837) registered in the ICDD database. (hereinafter referred to as "C-axis value of the database") long.

[0125] For example, the C-axis may be more than 2% longer than the database's C-axis value.

[0126] The lattice length of the C-axis is, for example, Above, preferably The above, more preferably above.

[0127] The magnetic particles according to one embodiment of the present invention are produced by aluminizing as in the above-mentioned first production method. In the aluminizing, a small amount of aluminum oxide is formed when aluminum infiltrates and alloys with the manganese particles.

[0128] Therefore, the magnetic particles according to one embodiment of the present invention have the characteristic of including aluminum oxide in addition to the manganese-aluminum alloy.

[0129] The presence ratio of aluminum oxide contained in the magnetic particles is preferably low. The lower limit is 0.1 mass % or more, and can be 1 mass %, 2 mass %, or 2.5 mass %, and the upper limit is preferably 15 mass % or less, and more preferably 10 mass % or less. If the presence ratio of aluminum oxide is small, the presence ratio of the non-magnetic phase decreases, and the presence ratio of the ferromagnetic phase τ phase can be increased.

[0130] In general, aluminum oxide tends to be localized on the outermost surface of magnetic particles, but aluminum oxide may also be present inside the magnetic particles.

[0131] The abundance ratio of the τ phase contained in the magnetic particles according to one embodiment of the present invention is in the range of 25 mass % to 99 mass %, preferably 30 mass % or more, and more preferably 50 mass % or more.

[0132] In the magnetic particles according to one embodiment of the present invention, the manganese-aluminum alloy may contain at least one of the ε phase, β phase, and γ phase in addition to the τ phase. However, the ε phase contained in the manganese-aluminum alloy is preferably 10% by mass or less.

[0133] Furthermore, the manganese-aluminum alloy contained in the magnetic particles according to one embodiment of the present invention may contain 65% by mass to 75% by mass of manganese and 25% by mass to 35% by mass of aluminum.

[0134] The magnetic particles involved in one embodiment of the present invention may be roughly spherical. At this time, the magnetic particles involved in one embodiment of the present invention may have an average particle size range of 7 μm to 500 μm, may be in the range of 10 μm to 300 μm, or may be in the range of 15 μm to 200 μm. When the average particle size of the magnetic particles is small, it is easy to increase the packing density during molding and easy to mold into a desired shape.

[0135] The magnetic particles according to one embodiment of the present invention having such characteristics can be suitably used in permanent magnets.

[0136] For example, a MnAl permanent magnet can be manufactured by molding and sintering a powder containing magnetic particles according to an embodiment of the present invention. In addition, the MnAl permanent magnet can have any shape, for example, a rectangular parallelepiped, an arched shape, a C-shape, etc.

[0137] The following describes a method for manufacturing a MnAl permanent magnet using magnetic particles according to an embodiment of the present invention, but the method for manufacturing a MnAl permanent magnet is not limited thereto, and other known methods may be used. For example, the MnAl permanent magnet according to this embodiment may be manufactured by hot working.

[0138] In the molding process, the finely pulverized powder is molded into a target shape. The molding can be performed by any method, but in the present embodiment, the magnetic particles are filled into a mold and pressurized. The obtained molded body is sintered in a vacuum or inert gas atmosphere to obtain a sintered body.

[0139] Here, dry molding in which magnetic particles are directly molded is shown, but wet molding in which a slurry obtained by dispersing magnetic particles in a solvent such as oil is molded may also be adopted. In addition, the shape of the molded body obtained by molding the magnetic particles may be any shape.

[0140] The MnAl permanent magnet according to the present embodiment obtained by the above method can be magnetized to become a MnAl permanent magnet product. The MnAl permanent magnet according to the present embodiment can be suitably used in motors, generators, and the like.

[0141] In addition, the method for producing the permanent magnet is not particularly limited as long as the effects of the present invention are not impaired, and various conventionally known production methods can be used.

[0142] Example

[0143] Examples of the present invention are described below. In the following description, Examples 1 to 5, Examples 21 to 24, Examples 31 to 33, and Examples 41 to 42 are examples. In addition, Examples 6 to 8 are comparative examples.

[0144] (Example 1)

[0145] The powder was prepared by the following method.

[0146] First, 69 g of manganese particles (average particle size 10 μm) and 31 g of aluminum particles (200 mesh) as an aluminum source were fully mixed with 300 ml of ethanol using a ball mill (10 mmφ Monomerlon ball) to obtain a first powder.

[0147] Next, ammonium chloride particles (0.5 mass%) as an activator and spherical alumina particles (74.6 mass%) with a diameter of 1 mmφ as a sintering inhibitor were added to the first powder (24.9 mass%) and then they were fully mixed to prepare a mixed powder.

[0148] In the mixed powder, the ratio of the content X of the aluminum particles to the content Y of the manganese particles (Y / (X+Y)) was 31% by mass in terms of mass ratio.

[0149] Next, the mixed powder was filled into a heat-resistant container with a lid. The filling rate of the aluminum oxide particles was calculated to be 74% by volume. In addition, the manganese particles, aluminum particles, and ammonium chloride particles were filled so as to occupy 80% of the remaining 26% of the voids.

[0150] Next, the interior of the heat-resistant container was depressurized and replaced with an argon atmosphere, and then the heat-resistant container was heated to 1210° C. After being maintained at 1210° C. for 10 hours, the heat-resistant container was furnace-cooled.

[0151] Thereafter, the treated mixture was taken out from the heat-resistant container and passed through a sieve having an aperture of 850 μm to remove the alumina powder, thereby obtaining a powder containing substantially spherical particles (hereinafter referred to as “powder A-1”).

[0152] (Example 2~Example 8)

[0153] Powders were prepared by the same method as in Example 1. However, in Examples 2 to 8, the conditions of the aluminizing treatment were changed from those in Example 1.

[0154] The obtained powders are referred to as "powder A-2" to "powder A-8", respectively.

[0155] The production conditions of powders A-1 to A-8 are collectively shown in Table 1 below.

[0156] [Table 1]

[0157]

[0158] (Example 21)

[0159] Powder was prepared in the same manner as in Example 1.

[0160] In Example 21, the ratio of the content X of the aluminum particles to the content Y of the manganese particles in the mixed powder (Y / (X+Y)) was set to 32% by mass.

[0161] In addition, the temperature of the aluminizing treatment was set to 1210°C.

[0162] The obtained powder is hereinafter referred to as "powder B-1".

[0163] (Example 22~Example 24)

[0164] Powder was prepared by the same method as in Example 21.

[0165] However, in Examples 22 to 24, the aluminizing treatment conditions were changed compared with those in Example 21.

[0166] The obtained powders are referred to as "powder B-2" to "powder B-4", respectively.

[0167] The production conditions of powders B-1 to B-4 are collectively shown in Table 2 below.

[0168] [Table 2]

[0169]

[0170] (Example 31)

[0171] Powder was prepared in the same manner as in Example 1.

[0172] In Example 31, the ratio of the content X of the aluminum particles to the content Y of the manganese particles in the mixed powder (Y / (X+Y)) was set to 33% by mass.

[0173] In addition, the temperature of the aluminizing treatment was set to 1210°C.

[0174] The obtained powder is hereinafter referred to as "powder C-1".

[0175] (Example 32~Example 33)

[0176] Powder was prepared by the same method as in Example 31.

[0177] However, in Examples 32 to 33, the aluminizing treatment conditions were changed compared to the case of Example 31.

[0178] The obtained powders are hereinafter referred to as "powder C-2" to "powder C-3", respectively.

[0179] The production conditions of powders C-1 to C-3 are collectively shown in Table 3 below.

[0180] [Table 3]

[0181]

[0182] (Example 41)

[0183] Powder was prepared in the same manner as in Example 1.

[0184] However, in Example 41, the composition of the mixed powder was changed compared with that of Example 1. In particular, the amount of the activator contained in the mixed powder was set to 1.5% by mass.

[0185] Furthermore, the aluminizing treatment conditions were changed compared to those in Example 1. In particular, the aluminizing treatment was carried out in a closed reaction vessel, and the pressure in the vessel during the treatment increased to a maximum of 3.25 atmospheres.

[0186] The obtained powder is hereinafter referred to as "powder D-1".

[0187] (Example 42)

[0188] Powder was prepared by the same method as in Example 41.

[0189] However, in Example 42, the aluminizing treatment conditions were changed compared with the case of Example 41. The obtained powder is hereinafter referred to as "powder D-2".

[0190] The production conditions of powders D-1 to D-2 are collectively shown in Table 4 below.

[0191] [Table 4]

[0192]

[0193] (evaluate)

[0194] The following evaluations were carried out using each powder.

[0195] (X-ray diffraction analysis)

[0196] X-ray diffraction analysis of each powder was performed using an X-ray diffractometer (SmartLab manufactured by Rigaku Corporation) and the mass fraction of each phase contained in the powder and the lattice constant of the τ phase were determined by Rietveld analysis based on the obtained diffraction pattern.

[0197] The Rietveld analysis was implemented using the program RIETAN-FP.

[0198] The profile function used was Toraya's dilation-segmentation Pseude-Voigt function, and the fitting was performed so that the reliability factor Rwp (R-weighted pattern) as a general standard was less than 10% with respect to the entire analysis range.

[0199] The analysis range is 2θ=10°~120°.

[0200] Figure 3 The X-ray diffraction results of powder A-1 at 30° to 90° are shown as an example.

[0201] Depend on Figure 3 It is found that powder A-1 mainly contains manganese-aluminum alloy and aluminum oxide. As manganese-aluminum alloy, τ phase and β phase are detected.

[0202] Table 5 below collectively shows the abundance ratios of the respective phases and the lattice constants of the τ phase calculated in the respective powders.

[0203] [Table 5]

[0204]

[0205] As can be seen from Table 5, Powders A-1 to A-5, Powders B-1 to B-4, Powders C-1 to C-3, and Powders D-1 to D-2 contain τ phase and alumina.

[0206] It is also found that in these powders, the τ phase exists in an amount of 25 mass % or more and the aluminum oxide exists in an amount of 1 mass % or more.

[0207] In addition, it can be seen that in powders A-1 to A-5, powders B-1 to B-4, powders C-1 to C-3, and powders D-1 to D-2, the length of the a-axis in the measured lattice constant is greater than the a value in the database. In particular, it can be seen that in all powders, the a-axis is shorter than the a value in the database by more than 0.2%.

[0208] In addition, it can be seen that in powders A-1 to A-5, powders B-1 to B-4, powders C-1 to C-3, and powders D-1 to D-2, the length of the C axis in the measured lattice constant is greater than the C value in the database. In particular, it can be seen that in all powders, the C axis is more than 2% longer than the C value in the database.

[0209] (Observation of Particles)

[0210] The cross section of the particles contained in each powder was observed using EPMA (manufactured by JEOL Ltd.: JXA-8230). In addition, element mapping of the cross section of the particles was performed using EPMA.

[0211] Figure 4 The result of elemental mapping of a cross section of powder A-1 is shown as an example.

[0212] From this mapping, it can be seen that aluminum oxide is concentrated on the outer surface of the particles.

[0213] (Mode of the Invention)

[0214] The present invention can have the following aspects.

[0215] (Method 1)

[0216] A method for producing magnetic particles comprising a manganese-aluminium alloy,

[0217] The manganese particles, the aluminum source, and the activator containing the halide and the anti-sintering agent are mixed to obtain a mixed powder.

[0218] The mixed powder is heated to a temperature in the range of 1000° C. to 1235° C., and the manganese particles are subjected to aluminizing treatment using gaps between the sintering inhibitors formed by the sintering inhibitors to obtain a treated mixture having magnetic particles containing a manganese-aluminum alloy.

[0219] In the above manganese-aluminum alloy, the ratio of aluminum to manganese (Al / Mn) is in the range of 25 / 75 to 35 / 65 by mass ratio.

[0220] The anti-sintering agent is removed from the treated mixture to recover the magnetic particles comprising the manganese-aluminum alloy.

[0221] (Method 2)

[0222] The method according to embodiment 1, wherein the activator comprises at least one selected from the group consisting of ammonium chloride, aluminum chloride and aluminum fluoride.

[0223] (Method 3)

[0224] The method according to aspect 1 or 2, wherein the amount of the activator is in a range of 0.1% by mass to 10% by mass based on the entire mixed powder.

[0225] (Method 4)

[0226] The method according to any one of embodiments 1 to 3, wherein the mixed powder is filled in a reaction container,

[0227] The filling rate of the anti-sintering agent with respect to the volume of the reaction container is in the range of 50% to 80%.

[0228] (Method 5)

[0229] The method according to any one of aspects 1 to 4, wherein the manganese particles have an average particle size of 5 μm to 300 μm.

[0230] (Method 6)

[0231] The method according to any one of aspects 1 to 5, wherein the average particle size of the aluminum source is 0.1 μm to 300 μm.

[0232] (Method 7)

[0233] The method according to any one of aspects 1 to 6, wherein the aluminizing treatment is performed under a pressurized environment.

[0234] (Method 8)

[0235] A method according to Embodiment 7, wherein the pressurized environment is achieved by introducing an inert gas into a sealed reaction container.

[0236] (Method 9)

[0237] A method according to aspect 7, wherein the pressurized environment is achieved by utilizing gas generated from the mixed powder filled in a closed reaction container.

[0238] (Method 10)

[0239] A magnetic particle comprising a manganese-aluminum alloy and aluminum oxide,

[0240] The aluminum oxide contained in the magnetic particles has a content in the range of 0.1 mass % to 15 mass %.

[0241] The manganese-aluminum alloy contained in the magnetic particles has a content in the range of 85 mass % to 99 mass %.

[0242] The above-mentioned manganese-aluminum alloy has a τ phase,

[0243] The abundance ratio of the τ phase contained in the magnetic particles is in the range of 25 mass % to 99 mass %.

[0244] (Method 11)

[0245] The magnetic particle according to embodiment 10, wherein the manganese-aluminum alloy further includes at least one of an ε phase, a β phase, and a γ phase.

[0246] (Method 12)

[0247] The magnetic particle according to embodiment 11, wherein the ε phase contained in the manganese-aluminum alloy is 10 mass % or less.

[0248] (Method 13)

[0249] The magnetic particle according to any one of aspects 10 to 12, wherein the manganese-aluminum alloy contains 65% by mass to 75% by mass of manganese and 25% by mass to 35% by mass of aluminum.

[0250] (Method 14)

[0251] The magnetic particle according to any one of aspects 10 to 13, wherein aluminum oxide is localized on the outermost surface of the magnetic particle.

[0252] (Method 15)

[0253] The magnetic particle according to any one of aspects 10 to 14, wherein the a-axis of the τ-phase lattice of the magnetic particle has an a-axis value of the lattice constant described in the database. short,

[0254] The C-axis value of the lattice constant of the τ phase of the magnetic particle is greater than the C-axis value of the lattice constant described in the database. long.

[0255] (Method 16)

[0256] The magnetic particle according to embodiment 15, wherein the a-axis of the τ-phase lattice of the magnetic particle is shorter than the a-axis of the lattice constant described in the database by 0.2% or more.

[0257] (Method 17)

[0258] The magnetic particle according to aspect 15 or 16, wherein the C-axis of the τ-phase lattice of the magnetic particle is longer than the C-axis of the lattice constant described in the database by 2% or more.

[0259] (Method 18)

[0260] A MnAl-based permanent magnet comprising the magnetic particles according to any one of aspects 10 to 17.

[0261] This application claims priority based on Japanese Patent Application No. 2022-091091 filed on June 3, 2022, the entire contents of which are incorporated herein by reference.

[0262] Explanation of symbols

[0263] 352 Manganese particles

[0264] 354 Aluminum Source

[0265] 358 anti-sintering agent

[0266] 365 gaps

Claims

1. A method for producing magnetic particles comprising a manganese-aluminum alloy, The manganese particles, the aluminum source, the activator including the halide and the anti-sintering agent are mixed to obtain a mixed powder, The mixed powder is heated to a temperature in the range of 1000° C. to 1235° C., and the manganese particles are subjected to aluminizing treatment using gaps between the sintering inhibitors formed by the sintering inhibitors to obtain a treated mixture having magnetic particles containing a manganese-aluminum alloy. in, In the manganese-aluminum alloy, the ratio of aluminum to manganese, i.e., Al / Mn, is in the range of 25 / 75 to 35 / 65 by mass ratio. The anti-sintering agent is removed from the treated mixture to recover the magnetic particles comprising the manganese-aluminum alloy.

2. The method according to claim 1, wherein: The activator comprises at least one selected from ammonium chloride, aluminum chloride and aluminum fluoride.

3. The method according to claim 1 or 2, wherein: The amount of the activator is in the range of 0.1% by mass to 10% by mass based on the entire mixed powder.

4. The method according to claim 1 or 2, wherein: The mixed powder is filled into a reaction container, The filling rate of the anti-sintering agent relative to the volume of the reaction container is in the range of 50% to 80%.

5. The method according to claim 1 or 2, wherein: The average particle size of the manganese particles is 5 μm to 300 μm.

6. The method according to claim 1 or 2, wherein: The average particle size of the aluminum source is 0.1 μm to 300 μm.

7. The method according to claim 1 or 2, wherein: The aluminizing treatment is performed under a pressurized environment.

8. The method according to claim 7, wherein: The pressurized environment is achieved by introducing an inert gas into a sealed reaction container.

9. The method according to claim 7, wherein: The pressurized environment is achieved by utilizing gas generated from the mixed powder filled in a closed reaction container.

10. A magnetic particle comprising a manganese-aluminum alloy and aluminum oxide, The aluminum oxide contained in the magnetic particles has a content in the range of 0.1 mass % to 15 mass %, The manganese-aluminum alloy contained in the magnetic particles has a content in the range of 85 mass % to 99 mass %, The manganese-aluminum alloy has a τ phase, The abundance ratio of the τ phase contained in the magnetic particles is in the range of 25 mass % to 99 mass %.

11. The magnetic particle according to claim 10, wherein The manganese-aluminum alloy further includes at least one of an ε phase, a β phase, and a γ phase.

12. The magnetic particle according to claim 11, wherein The manganese-aluminum alloy contains 10 mass % or less of the ε phase.

13. The magnetic particle according to claim 10 or 11, wherein The manganese-aluminum alloy contains 65 mass % to 75 mass % of manganese and 25 mass % to 35 mass % of aluminum.

14. The magnetic particle according to claim 10 or 11, wherein Aluminum oxide is localized on the outermost surface of the magnetic particles.

15. The magnetic particle according to claim 10 or 11, wherein The a-axis value of the lattice constant of the τ phase lattice of the magnetic grain is greater than the a-axis value of the lattice constant recorded in the database. short, The C-axis value of the lattice constant of the τ phase lattice of the magnetic grain is greater than the C-axis value of the lattice constant recorded in the database. long.

16. The magnetic particle according to claim 15, wherein The a-axis of the τ-phase lattice of the magnetic grain is shorter than the a-axis of the lattice constant recorded in the database by 0.2% or more.

17. The magnetic particle according to claim 15, wherein The C-axis of the τ-phase lattice of the magnetic grain is longer than the C-axis of the lattice constant recorded in the database by 2% or more.

18. A MnAl-based permanent magnet comprising the magnetic particles according to claim 10 or 11.

Citation Information

Patent Citations

  • MANUFACTURING METHOD OF MnAl ALLOY

    JP2019044265A

  • Light importance caching using spatial hashing in real-time ray tracing application

    JP2022091091A